Analisis pemanfaatan Youtube sebagai Media Pembelajaran dalam Tema 7 Subtema 1 Kelas IV SDN Jatingaleh 02 Semarang - Komariyah Komariyah; Ikha Listyarini; Henry Januar Saputra (STKIP Andi Matappa Pangkep, 2022)
The aim of this study is to analyze the use of youtube as a learning medium at SDN Jatingaleh 02 Semarang for 4th class. Which is descriptive for the teachers. The type of this research is descriptive qualitative with data collection techniques through interviews, observation, student questionnaires, and documentation. The research subjects are teachers and students at 4th class. The results are: 1) planning and choosing videos before teaching, 2) implementation by displaying and sharing by WA’s group. This learning process requires the teachers designing activities and providing interesting objectives. The conclusion of youtube as a learning medium can give positive impact for students, by stimulating, can to make the students comfortable, can increase students motivation, focusing, insight, and knowledge.